Silencing SCAMP1-TV2 Inhibited the Malignant Biological Behaviors of Breast Cancer Cells by Interaction With PUM2 to Facilitate INSM1 mRNA Degradation - Tao, Wei; Ma, Jun; Zheng, Jian; Liu, Xiaobai; Liu, Yunhui; Ruan, Xuelei; Shen, Shuyuan; Shao, Lianqi; Chen, Jiajia; Xue, Yixue (Frontiers in Oncology, 2020)
Molecular-targeted therapy plays an important role in the combined treatment of breast cancer. Long non-coding RNA (LncRNA) plays a significant role in regulating breast cancer progression. The present study is to reveal the potential roles and molecular mechanism that the SCAMP1-TV2 has in breast. CCK-8, RIP and RNA pull-down assays were employed to determine the interactions between SCAMP1-TV2 and PUM2. The luciferase reporter assays and ChIP assays were used to get to know the effect of INSM1 directly on the SASH1 promoter. Silenced SCAMP1-TV2 inhibited the proliferation, migration，and invasion of breast cancer cells, and promoted cell apoptosis. Meanwhile, SCAMP1-TV2 down-regulation decreased its binding to PUM2 and increased the binding of PUM2 to INSM1 mRNA, thus promoting the degradation of INSM1 mRNA. Silencing INSM1 decreased its inhibitory effect on SASH1 transcription and inhibited the PI3K/AKT signaling pathway. The xenograft tumor growth in a nude mice was significantly inhibited by the silencing of SCAMP1-TV2 in combination with the over-expression of PUM2. SCAMP1-TV2/PUM2/INSM1 pathway plays an important role in regulating the biological behavior of breast cancer cells.